2013
DOI: 10.1111/sltb.12058
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐Related and Protective Correlates of Nonsuicidal Self‐Injury and Co‐Occurring Suicide Attempts among Incarcerated Women

Abstract: Individual and environmental correlates of nonsuicidal self-injury (NSSI) and co-occurring suicide attempts (SA) among incarcerated women (N = 104) were examined. Participants completed measures of putative risk and protective factors, including coping styles, childhood maltreatment, and hopelessness. Results indicated that active coping was uniquely, negatively associated with the presence and frequency of NSSI, whereas avoidant coping and childhood physical/emotional abuse were positively associated with NSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Future research on the transition from childhood to adolescence is important, given NSSI onset typically occurs during this period of development. 118,119 Fourth, only seven studies 4,26,37,48,60,73,76 allowed for analyses of “pure” NSSI (i.e., unconfounded by its naturally high co-occurrence with suicide attempt history 5,120 ) in relation to childhood maltreatment. As suicidal behavior is also associated with childhood maltreatment, 121 future research cleanly separating it from NSSI is required accurately to assess the latter in relation to childhood maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Future research on the transition from childhood to adolescence is important, given NSSI onset typically occurs during this period of development. 118,119 Fourth, only seven studies 4,26,37,48,60,73,76 allowed for analyses of “pure” NSSI (i.e., unconfounded by its naturally high co-occurrence with suicide attempt history 5,120 ) in relation to childhood maltreatment. As suicidal behavior is also associated with childhood maltreatment, 121 future research cleanly separating it from NSSI is required accurately to assess the latter in relation to childhood maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, although non-suicidal and suicidal deliberate self-harm have been found to co-occur [ 1 ], some researchers suggest that they are associated with different risk factors [ 1 , 57 ]. For example, among incarcerated women with a history of non-suicidal deliberate self-harm, hopelessness was more strongly associated with the frequency of suicide attempts than that of non-suicidal deliberate self-harm [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although non-suicidal and suicidal deliberate self-harm have been found to co-occur [ 1 ], some researchers suggest that they are associated with different risk factors [ 1 , 57 ]. For example, among incarcerated women with a history of non-suicidal deliberate self-harm, hopelessness was more strongly associated with the frequency of suicide attempts than that of non-suicidal deliberate self-harm [ 57 ]. Further, among adolescents being treated for depression; poor family functioning at entry into the program was associated only with suicide attempts, while being younger, female, having anxiety disorders and hopelessness was associated with only non-suicidal deliberate self-harm [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated rates of self-injury have been noted in incarcerated populations (Chapman, Gratz, & Turner, 2014 ; Smith & Kaminski, 2011 ) including adolescents in secure care (Casiano, Katz, Globerman, & Sareen, 2013 ; Dixon-Gordon, 2011 ). A higher rate of self-injury in adolescent forensic samples is consistent with their increased prevalence of both psychiatric disorder (e.g., Wasserman, McReynolds, Schwalbe, Keating, & Jones, 2010 ) and trauma exposure (Wasserman & McReynolds, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risks linked to generally-defined self-injury in community samples of adolescents include internalizing conditions (e.g., Major Depressive Disorder, Post-traumatic Stress Disorder; Muehlenkamp & Gutierrez, 2007 ; Ross & Heath, 2002 ), externalizing behaviors (e.g., Conduct Disorder, Marijuana Abuse/Dependence; see Jacobson & Gould, 2007 for a review), and history of child maltreatment (Chapman et al, 2014 ; Fliege, Lee, Grimm, & Klapp, 2009 ; Gomez, Becker-Blease, & Freyd, 2015 ; Lang & Sharma-Patel, 2011 ). Several recent studies reported significant elevations in trauma exposure among adolescents who self-harm (Ellis et al, 2002 ; Kenny et al, 2008 ; McReynolds & Wasserman, 2011 ; Morgan & Hawton, 2004 ).…”
Section: Introductionmentioning
confidence: 99%